Use of remote sensing and UAV for the management of degraded ecosystems: The case study of overgrazing in Randi Forest, Cyprus - Themistocleous, Kyriacos; Papadavid, George; Christoforou, Michalis; Agapiou, Athos; Andreou, Kostas; Tsaltas, Dimitrios; Hadjimitsis, Diofantos G. (My University, 2014)
This paper provides the results obtained by using satellite imagery and UAV data for managing a degraded system over Randi Forest in Cyprus. Landsat TM/ETM+ and GeoEye images have been used to retrieve several indices with the main aim to managing the overgrazed area. Aerial photographs were acquired in order to document and monitor the overgrazed areas, which also include seasonal changes in vegetation and soil. UAVs were used to create ortho-photos and DEMS. Satellite images were used to conduct NDVIs of the study area. The resulting findings provide a detailed image of the specific location of overgrazed areas. The results of the study can be used for decision makers to establish effective strategies to avoid similar scenarios of overgrazing in other parts of Cyprus.This study was funded by the FP7 programme CASCADE Project on sudden and catastrophic shifts in dryland Mediterranean ecosystems (2012-2017).
Keywords: DEM; NDVI; Overgrazing; Spectroscopy; UAV